2003
DOI: 10.1116/1.1564035
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of thin Ag and Au films on Si(111) using thin copper silicide buffer layers

Abstract: Articles you may be interested inSchottky barrier height measurements of Cu/Si(001), Ag/Si(001), and Au/Si(001) interfaces utilizing ballistic electron emission microscopy and ballistic hole emission microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…This interlayer relaxes the lattice mismatch between Cu and Si, enabling epitaxial growth . The epitaxial growth of silver (Ag) thin films on copper silicide interlayers has also been reported. , However, epitaxial Ag thin films prepared using this approach exhibited excessive hydrocarbon selectivities uncharacteristic of Ag at potentials cathodic of −1 V vs RHE (see section SI-7). Ion-scattering spectroscopy (ISS) revealed that this is due to the presence of Cu on the surface of these electrodes after CO 2 reduction, which most likely reaches the electrode surface as a consequence of adsorbate induced segregation from the copper silicide interlayer .…”
Section: Resultsmentioning
confidence: 99%
“…This interlayer relaxes the lattice mismatch between Cu and Si, enabling epitaxial growth . The epitaxial growth of silver (Ag) thin films on copper silicide interlayers has also been reported. , However, epitaxial Ag thin films prepared using this approach exhibited excessive hydrocarbon selectivities uncharacteristic of Ag at potentials cathodic of −1 V vs RHE (see section SI-7). Ion-scattering spectroscopy (ISS) revealed that this is due to the presence of Cu on the surface of these electrodes after CO 2 reduction, which most likely reaches the electrode surface as a consequence of adsorbate induced segregation from the copper silicide interlayer .…”
Section: Resultsmentioning
confidence: 99%
“…We have observed the wavevector quantization in LaSrCuO films thinner than 12 unit cells grown on SrTiO 3 substrates. Low energy dispersions were determined in situ for different photon energies by angle resolved photoemission spectroscopy.…”
Section: Fermi Surface Determination From Wavevector Quantization In mentioning
confidence: 80%
“…[1][2][3][4] The effect is due to the discrete nature of the energy spectra associated with the standing wave solutions of the Schrödinger equation in a finite medium. 5 However, due to the roughness of their surfaces and interfaces, it is often not observed in very thin films.…”
Section: Fermi Surface Determination From Wavevector Quantization In mentioning
confidence: 99%